Recent Trends in Private Equity Acquisition of Orthopaedic Practices in the United States. Issue 8 (15th April 2022) - Boddapati, Venkat; Danford, Nicholas C.; Lopez, Cesar D.; Levine, William N.; Lehman, Ronald A.; Lenke, Lawrence G.
Abstract : Background: Private equity acquisition of medical specialty practices has increased in recent years. With the projected increase in the volume of elective, ambulatory orthopaedic procedures, especially in the outpatient setting, private equity firms are increasingly investing in orthopaedic practices. The purpose of this cross-sectional study was to report recent trends and variations in acquisitions of US orthopaedic practices by private equity firms and other institutional investors (venture capital firms, trusts, and large investment companies). Methods: Acquisition data through January 1, 2020, were collected and analyzed using various financial databases, supplemented with publicly available information from financial news outlets, press releases, and financial analyst and industry reports. Disclosed financing data were also included, in addition to pertinent geographic information (state, city, and zip code) of the target practices. Results: Between 2004 and 2019, 41 orthopaedic practices and surgeon groups across 22 states were acquired by 34 private equity and other investment firms. A significant increase was observed in the number of acquisitions between 2017 and 2019, consisting of 70.7% of total transactions during the study period, with a statistically significant upward yearly trend ( P = 0.002). The compound annual growth rate in acquisition volume was 29.2% during the study period. A disproportionate share of private equity acquisitions took place in the South, where more than half (51.2%) of the total transactions took place. Firms were markedly more likely to acquire or invest in practices located in major metropolitan areas (population more than 1 million) compared with those in mid-sized or rural areas (70.7%, 17.1%, 12.2%, respectively; P < 0.001). Conclusions: Private equity acquisition of orthopaedic surgery practices has increased markedly in recent years. The effect of private equity acquisition on physician independence, practice management, and procedure reimbursement remains unclear and may be important to explore as practice management evolves. Level of evidence: Prognostic Level III